Methanol steam reforming catalysts derived by reduction of perovskite-type oxides LaCo1−x−yPdxZnyO3±δ. Issue 5 (13th October 2015) - Kuc, Jagoda; Neumann, Matthias; Armbrüster, Marc; Yoon, Songhak; Zhang, Yucheng; Erni, Rolf; Weidenkaff, Anke; Matam, Santhosh Kumar
Abstract : Pd–Zn nanoparticles are synthesized by reduction of LaCo1− x − y Pd x Zn y O3± δ for methanol steam reforming and they can be reintegrated into the perovskite crystal on reoxidation. Abstract : Methanol steam reforming (MSR) catalysts are derived from perovskite-type oxides LaCo1− x − y Pd x Zn y O3± δ by reductive pretreatment. The unsubstituted LaCoO3± δ (LCO) and LaCo1− x − y Pd x Zn y O3± δ (Co substituted with Pd and/or Zn) are synthesized by a citrate method and characterized by different techniques. The perovskite-type oxides exhibit a rhombohedral crystal structure and a comparable surface area (≈8.5 (±2) m 2 g −1 ). The temperature-programmed reduction (TPR) shows low (100 °C < T < 450 °C) and high ( T > 450 °C) temperature reduction events that correspond to partial and complete reduction of the non-rare-earth metal ions, respectively. At high temperatures, Pd–Zn alloy nanoparticles are formed exclusively on Pd- and Zn-containing LaCo1− x − y Pd x Zn y O3± δ, as evident from high angular annular dark-field scanning transmission electron microscopy (HAADF-STEM). The CO2 -selective MSR performance of the catalysts strongly depends on the reductive pretreatment temperature, catalyst composition ( i.e., the Pd : Zn molar ratio and the degree of Co substitution) and reaction temperature. Only LaCo1− x − y Pd x Zn y O3± δ catalysts show a low-temperature CO2 selectivity maximum between 225 and 250 °C, while all catalysts present similar high-temperature selectivity maxima at T > 400 °C. The former is missing on LCO, LaCo1− x Pd x O3± δ or LaCo1− y Zn y O3± δ . Pd–Zn nanoparticles facilitate Zn(OH)2 and Co(OH)2 formation exclusively on LaCo1− x − y Pd x Zn y O3± δ, as evident from in situ XRD under steam atmosphere. This indicates the important role of Pd–Zn nanoparticles in the low-temperature CO2 selectivity, which is improved from 0 to 76% at 225 °C on LCO and LaCo0.75 Pd0.125 Zn0.125 O3± δ, respectively. The high-temperature CO2 selectivity is governed by the bulk catalyst composition and the occurrence of reverse water gas shift reaction.